2009
DOI: 10.1016/j.semarthrit.2008.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Medication Adherence of Patients with Selected Rheumatic Conditions: A Systematic Review of the Literature

Abstract: Objective-Nonadherence with medication treatment has been found to occur in large proportions of patients with a broad range of chronic conditions. Our aim was to perform a systematic review of the literature examining adherence with treatments for inflammatory rheumatic conditions to assess the magnitude of the problem in this patient population.Methods-A MEDLINE search of English language literature was performed to identify studies published between January 1, 1985 and November 30, 2007 that evaluated adher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
70
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(73 citation statements)
references
References 33 publications
(5 reference statements)
1
70
0
2
Order By: Relevance
“…Problems with cognitive functioning, concerns about potential adverse effects of medication, and age were the best predictors of nonadherence. Treatment nonadherence has been identified as a substantial problem in patients with chronic inflammatory rheumatic diseases (32). However, few studies have focused on treatment nonadherence in SLE patients specifically and no prior studies have included self-report adherence questionnaires that have been validated for use in SLE patients.…”
Section: Discussionmentioning
confidence: 99%
“…Problems with cognitive functioning, concerns about potential adverse effects of medication, and age were the best predictors of nonadherence. Treatment nonadherence has been identified as a substantial problem in patients with chronic inflammatory rheumatic diseases (32). However, few studies have focused on treatment nonadherence in SLE patients specifically and no prior studies have included self-report adherence questionnaires that have been validated for use in SLE patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although several systematic or comprehensive reviews have evaluated adherence to DMARD in general 7,17,18 , only 1 systematic study, to our knowledge, has specifically evaluated MTX adherence (but not persistence) in patients with RA 13 . Given the prevalence of MTX use and its involvement in combination treatment with biologics, it is important to understand factors that may cause patients to be nonadherent or to discontinue treatment.…”
mentioning
confidence: 99%
“…Indeed, this notion is supported by previous studies demonstrating that poor treatment persistence of biologics can blunt the effectiveness [22,23]. While several studies have revealed that overall treatment persistence of biologic agents in elderly RA patients is not inferior to that in younger RA patients [24,25], large variation in treatment persistence as well as reasons for discontinuation among different biologic agents have been noted [25,26].…”
Section: Introductionmentioning
confidence: 77%